Access to basic urban services in secondary towns in Chad: An evaluative approach based on data from the town of Pala - Patouki, Sing-Non Bourdannet; Ndonaye, Allarané; N’Dilbé, Tob-Ro; Naringué, François Teadoum; Follygan, Hetcheli (Edelweiss Applied Science and Technology, 2025)
Urban growth in Chad's secondary towns, although less pronounced than in the capital, presents significant challenges for access to urban services essential for residents' well-being and sustainable urban development. This study focuses on access to these services in the town of Pala, adopting an evaluative approach to identify the difficulties faced by residents and the coping strategies they employ. A mixed methodology was used, combining qualitative and quantitative data, with logistic regression analysis and other statistical tests. The results reveal that only 15% of the population has access to drinking water, while 70% rely on traditional wells. In terms of sanitation, 60% of inhabitants use inappropriate traditional latrines, and 66% of wastewater is discharged into the street or into nature due to a lack of sewerage systems. Regarding education, 67% of school-age children do not have access to adequate teaching, and 60% of educational infrastructure is in poor condition. These findings highlight the need for increased action by local stakeholders and the government to improve access to these critical services.